(untitled) (Castilla. Estudios de Literatura, 2020)
The role played by emotions in classic rhetoric builds up a system that remains stable until mid XVIII Century. From this moment on, it suffers a deep reorganization that affects all of its components. The lexicographic study of entries that are related to emotions in Spanish dictionaries of the Enlightenment, focusing on the terms "moción" and "pasión", enables us to see the dynamics of those changes. Amongst them, the disappearance of movement and action in the process of emotional transmission from speaker to listener or the relocation of the emotional "pathos", which passes from the listener’s to the speaker’s sphere stand out.